Re-establishing peasant roots, deconstructing upper-class identities. "In the name of Jakub S." by Monika Strzępka and Paweł Demirski - Berkan, Krystyna (To Tell the History: Polish Contemporary Dramaturgy after 2006, 2023)
The aim of this article is to analyze the drama In the name of Jakub S. (W imię Jakuba S.) by Paweł Demirski and the performance under the same title, staged in Teatr Dramatyczny in Warsaw in 2011. The artists – the author Paweł Demirski and the director, Monika Strzępka – argued that there exists a parallel between economic serfdom and contemporary capitalist exploitation. At the same time, they criticized the leading historical discourse that focuses on the upper classes (such as nobility). As a counterproposal, they attempted to create a narrative about the subaltern groups, foremostly peasants. They emphasized the significance of events such as the Galician Slaughter (Rabacja Galicyjska) of 1846, during which this social class revealed its agency. I examine if such theses can be considered seriously regarding historical knowledge. An important context to me are the current Polish historical and sociological publications and polemics about the so-called people’s history. At the same time, I ask if the ideas of Strzępka and Demirski were clear for the auditorium and how they corresponded with the viewers’ particular experiences.